Mukhalafatuhu li al-Hawadith Menurut Perspektif Shurrah Matan Jawharah al-Tawhid: Mukhalafatuhu li al-Hawadith According to Commentators of Matn Jawharah al-Tawhid - Hassan Basri, Muhammad Nasri; Shuhari, Mohd Hasrul; Engku Wok Zin, Engku Ibrahim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
This article discusses one of the necessary attributes of Allah SWT, namely mukhalafatuhu li al-hawadith according to shurrah (commentators) of matn Jawharah al-Tawhid. This qualitative study uses the method of comparative analysis through Jawharah al-Tawhid narration based on the views of al-Imam Ibrahim bin Hasan al-Laqani and other scholars who have discussed this text in their works. The discussion focuses on the methodology of scholars in describing this text on the nature of mukhalafatuhu li al-hawadith. They try to expound the correct meaning of this attribute in line with the doctrine of Ahl al-Sunnah wa al-Jama’ah. As a result, Muslims are able to understand that there is a very significant difference between Allah SWT and His creatures. All scholars that are studied agreed that Allah SWT is totally different with al-hawadith in every aspect.